Increased Career Self-Efficacy Predicts College Students' Motivation, and Course and Major Satisfaction. (August 2014) - Komarraju, Meera; Swanson, Jane; Nadler, Dustin
In two studies, we assessed the effectiveness of a careers in psychology course in increasing students' career decision self-efficacy, and the role of increased career decision self-efficacy in predicting motivation as well as course, and major satisfaction. Students completed assignments involving career self-exploration, planning future semesters, resume creation, job search, interviewing a professional in the field, exploring subfields, visiting a research lab, and internship opportunities. In Study 1, paired-sample t -tests for 79 students revealed significant increases in career decision self-efficacy. In Study 2, at pretest and posttest, 226 students completed measures of career decision self-efficacy, self-determined motivation, career information, course, and major satisfaction. Regression analyses indicated that career self-efficacy explained significant variance in self-determined motivation, course, and major satisfaction. Further, perceived gains in career information mediated the relationship between increased career self-efficacy and self-determined motivation, course, and major satisfaction. Finally, assignments providing concrete professional experiences predicted increases in career self-efficacy.